2018
DOI: 10.1371/journal.pone.0195796
|View full text |Cite|
|
Sign up to set email alerts
|

Type-2 diabetic aldehyde dehydrogenase 2 mutant mice (ALDH 2*2) exhibiting heart failure with preserved ejection fraction phenotype can be determined by exercise stress echocardiography

Abstract: E487K point mutation of aldehyde dehydrogenase (ALDH) 2 (ALDH2*2) in East Asians intrinsically lowers ALDH2 activity. ALDH2*2 is associated with diabetic cardiomyopathy. Diabetic patients exhibit heart failure of preserved ejection fraction (HFpEF) i.e. while the systolic heart function is preserved in them, they may exhibit diastolic dysfunction, implying a jeopardized myocardial health. Currently, it is challenging to detect cardiac functional deterioration in diabetic mice. Stress echocardiography (echo) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 40 publications
(49 reference statements)
0
28
0
Order By: Relevance
“…MAO-dependent oxidative stress may lead to the inhibition of aldehyde dehydrogenase 2 (ALDH2) resulting in further accumulation of toxic and reactive aldehydes (37). In that regard, it has been demonstrated that stimulation of ALDH2 activity protects from streptozotocin-induced cardiac damage (172), suggesting that accumulation of aldehydes may promote cardiac remodeling in diabetes independently or in concert with high ROS levels (173).…”
Section: Monoamine Oxidasesmentioning
confidence: 99%
“…MAO-dependent oxidative stress may lead to the inhibition of aldehyde dehydrogenase 2 (ALDH2) resulting in further accumulation of toxic and reactive aldehydes (37). In that regard, it has been demonstrated that stimulation of ALDH2 activity protects from streptozotocin-induced cardiac damage (172), suggesting that accumulation of aldehydes may promote cardiac remodeling in diabetes independently or in concert with high ROS levels (173).…”
Section: Monoamine Oxidasesmentioning
confidence: 99%
“…In fact, a recent clinical study in East Asians with ALDH2*2 mutation demonstrated an association between ALDH2*2 and HFpEF in patients having diabetes and other comorbidities [17]. Even before this study, we were the rst to demonstrate that ALDH2*2 mutant mice with type-2 DM exhibited exacerbation of HFpEF features relative to wild-type mice with type-2 DM [10]. Thus, we employed the same high-fat diet (HFD)-fed ALDH2*2 mutant diabetic mice in this study as well.…”
Section: Introductionmentioning
confidence: 75%
“…ALDH2*2 knock-in mutant mice (with C57BL/6J background) either male or female around 3-4 months of age were fed an HFD (60% of calories from fat, D12492, Research Diets) as we published earlier [10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through this enzymatic function, the human ALDH isoenzymes participate in biochemical pathways regulating alcohol detoxification, neuronal function, vitamin and amino acid metabolism and the synthesis of γ-aminobutyric acid and retinoic acid [1][2][3]. Abnormalities in the catalytic activity of ALDHs have been associated with severe disorders, including cancer, neurodegenerative conditions, cardiovascular diseases, diabetes, and stroke [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%